PENGGUNAAN MODEL JIGSAW DALAM MENGEMBANGKAN KEAKTIFAN BELAJAR PPKN X MIPA 4 SMAN 8 PONTIANAK - Yurika Noviana Utami; Bambang Budi Utomo; Thommy Sastra Atmaja (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This study aims to describe the planning, implementation, assessment, and learning activeness students by using the Jigsaw model in PPKn subjects X MIPA 4 SMAN 8 Pontianak. This type of research is qualitative with descriptive methods. The subject of this research is X MIPA 4, amounting 32 students. Data collection techniques, namely: observation, interviews and documentation. Based results of the study that: 1. In the teacher's RPP is in accordance 2013 curriculum RPP and the preparation of the teacher's RPP has designed learning that can develop student learning activities. 2. Implementation of learning at the first and second meeting, the teacher has implemented according to the RPP and stages of the Jigsaw model. 3. Assessment of the Jigsaw model in the RPP, namely: Attitudes, Knowledge, and Skills. The aspects related to learning activeness are skills because contain indicators of learning activeness. 4. Students active learning observations average scores obtained at the first meeting are 6 of 8 indicators with good assessment criteria and the second meeting is 7 of 8 indicator very good assessment criteria. Therefore, it can be concluded that the Jigsaw model can develop students learning activeness in PPKn subjects in class X MIPA 4 SMAN 8 Pontianak. Keywords: Jigsaw Model, Learning Activeness, PPkn